Natural killer cells - Kennedy, Philippa (Henry Stewart Talks, 2021)
The role of NK (Natural Killer) cells, Where NK cells are found, How NK cells kill, NK cell activation and inhibition, Genetic studies in NK cells, NK cells and modern therapies